EVALUATING THE NATIONAL SECURITY AND ECONOMIC CONSEQUENCES OF U.S. RESTRICTIONS ON FOREIGN DRONES - Hussain, Naveed (The journal of contemporary issues in business and government, 2025)
This work investigates not only about the increasing use of overseas produced drones (especially of Chinese and Russian companies) in the U.S., but also the potential consequences on the national security, sectors and economic strength. The Commerce Department has restricted these drones on the grounds of spying threats, vulnerability to cyber-security risks as well as the integration of AI (Artificial Intelligence) chips inside them. These risks involve things like data exfiltration, AI model poisoning and firmware backdoors that could all impact sensitive data and national security. But the ban has also presented extensive operational and economic hardships, particularly in sectors that depend on drones, including agriculture, emergency response and infrastructure inspections. These are companies that rely on low-cost foreign drones such as DJI and this need for affordable local alternatives has hampered the fortunes for them leading to higher operational costs and inefficiencies. The paper goes on to argue that these issues prompt a consideration of an equilibrium approach to regulation. A total ban on all foreign drones may be unwise, but a more selective policy that focuses on models we know represent a risk to our national security could be used to neutralize these threats without damaging vital areas of the economy. The research also suggest that there should be investment for manufacturing of drones domestically, robust cyber security for AI managed drones and public-private partnership to promote innovation in domestic UAV sector. Doing so will allow the U.S. government to protect national security while minimizing economic dislocation and maintaining forward momentum in areas that rely on drone technology.